IMPLEMENTATION OF SUSTAINABILITY REPORTING IN PUBLIC ADMINISTRATION OF THE UKRAINE’S FORESTRY SECTOR - Zongaym, Yuliia (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
This article investigates the strategic prospects for integrating sustainability reporting (ESG) into the public administration of Ukraine’s forestry sector as a key driver for modernization. The study provides a comprehensive analysis of European expertise, with a particular focus on Spanish legislative frameworks and administrative practices. The author justifies the imperative for transparent non-financial reporting as a key component for ensuring Ukraine’s post-war green recovery and its seamless integration into the European Single Market. Special attention is given to the alignment of forestry management with the Corporate Sustainability Reporting Directive (CSRD) to enhance accountability and attract international investment for sustainable development.